When culture speaks louder than words: Cultural intelligence and communicative misalignment in asylum interview interpreting - Munyangeyo, Théophile (My University, 2026)
This paper reconceptualises public service interpreting (PSI) in asylum interviews by positioning cultural miscommunication as a structurally embedded feature of triadic: interaction among interpreters, asylum seekers, and immigration officers. Departing from conduit and equivalence-based approaches, the study integrates interactional sociolinguistics, social semiotics, and practice theory to examine how meaning is negotiated through culturally situated and multimodal communicative resources that extend beyond language alone. Drawing on the theoretical contributions of Erving Goffman, Pierre Bourdieu, and Gunther Kress, interpreting is framed as an interactional practice operating within asymmetrical institutional fields in which communicative authority and epistemic legitimacy are unevenly distributed. The analysis is based on qualitative narratives from interpreters working in asylum settings. Findings demonstrate that communicative breakdowns are systematic rather than incidental, emerging from divergences in narrative organisation, affective expression, and culturally embedded communicative norms. Within institutional frameworks that prioritise linearity and linguistic transparency, silence, hesitation, and culturally specific forms of expression are frequently misinterpreted, which produces epistemic distortion and negative credibility assessments. Although interpreters may possess the cultural intelligence and linguistic competences required to anticipate and mediate such misunderstandings, their capacity to intervene is constrained by institutionalised expectations of communicative neutrality, which limits the use of culturally informed inferencing and repair strategies. The study argues that interpreting entails the ongoing management of alignment, framing, and contextualisation. It concludes by advocating a shift from linguistic accuracy toward multimodal meaning equivalence and by redefining interpreters as epistemic actors within asylum decision-making processes, with implications for PSI theory and interpreter training.
PUBLISHED
https://doi.org/10.37745/gjahss.2013/vol14n36592
Keywords: Cultural intelligence; public service interpreting; multimodal communication; interpreter agency; asylum interviews; triadic interaction; epistemic distortion; Inclusive Society; Cultural Identity; Language and/or Literature, Modern; Translation; Communication